X-ray photoelectron spectroscopy characterization of aerosol particles in Antarctica. Issue 5 (30th April 2015) - Rella, Simona; Malitesta, Cosimino
Abstract: Qualitative and quantitative analysis of surface species on size-segregated atmospheric particulate collected in Antarctica during the 2010–11 summer was performed by X-ray photoelectron spectroscopy (XPS). This represents the first example of surface characterization of Antarctic aerosols. The size class with particle cut-off diameter of 3 μm was richest in terms of chemical elements. Peculiar findings of the application included detection of Ca (possibly surface-segregated) and surface enrichment of Mg. The determination of nitrate, ammonium and sulphate species on collection filters provides evidence for a possible advantage of XPS over more laborious techniques (e.g. ion chromatography). The presence of these species is in reasonable agreement with other recent reports from Antarctica.